2021
DOI: 10.1371/journal.pone.0250624
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of smartwatch-based activity recognition models for rigging crew workers on cable logging operations

Abstract: Analysis of high-resolution inertial sensor and global navigation satellite system (GNSS) data collected by mobile and wearable devices is a relatively new methodology in forestry and safety research that provides opportunities for modeling work activities in greater detail than traditional time study analysis. The objective of this study was to evaluate whether smartwatch-based activity recognition models could quantify the activities of rigging crew workers setting and disconnecting log chokers on cable logg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 100 publications
(196 reference statements)
1
13
1
Order By: Relevance
“…While no studies were identified to evaluate the industry’s needs for such technologies in Romania, some small-scale tests have already proven their usefulness, in terms of cost saving and safety [ 8 , 9 , 10 ]. In addition, the operational level has been identified in international forestry to be one of the potential beneficiaries of sensor-based and machine learning implementations [ 8 , 9 , 10 , 11 , 12 ], which enabled significant resource savings and safety improvements. At this level, manual-dominated tasks have been approached in forestry under the umbrella of the so-called human activity recognition, which has been implemented by the use of various data collection platforms and machine learning techniques e.g., [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…While no studies were identified to evaluate the industry’s needs for such technologies in Romania, some small-scale tests have already proven their usefulness, in terms of cost saving and safety [ 8 , 9 , 10 ]. In addition, the operational level has been identified in international forestry to be one of the potential beneficiaries of sensor-based and machine learning implementations [ 8 , 9 , 10 , 11 , 12 ], which enabled significant resource savings and safety improvements. At this level, manual-dominated tasks have been approached in forestry under the umbrella of the so-called human activity recognition, which has been implemented by the use of various data collection platforms and machine learning techniques e.g., [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the operational level has been identified in international forestry to be one of the potential beneficiaries of sensor-based and machine learning implementations [ 8 , 9 , 10 , 11 , 12 ], which enabled significant resource savings and safety improvements. At this level, manual-dominated tasks have been approached in forestry under the umbrella of the so-called human activity recognition, which has been implemented by the use of various data collection platforms and machine learning techniques e.g., [ 11 , 12 ]. A similar approach has been used to monitor tool or machine-supported tasks, at least when such machines were not equipped with built-in production monitoring systems [ 8 , 9 , 10 , 13 ]; this approach still justifies its relevance due to the low to intermediary mechanization level of forest operations that still prevails in many parts of the world [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a smartphone secured to the belt of a timber faller, the activity recognition model characterized manual felling work elements and delay with accuracies between 65.9% and 99.6%. More recently, smartwatch sensors have been successfully used to develop activity recognition models for rigging crew workers setting and disconnecting log chokers on cable logging operations [ 57 ]. These new smart device-based activity recognition applications show promise for further integration into forest industries.…”
Section: Introductionmentioning
confidence: 99%